Peningkatan Pemahaman Pola Asuh Melalui Strategi Inquiry dalam Program Keluarga Harapan di Desa Pakutandang, Kecamatan Ciparay, Kabupaten Bandung - Handoko, Indra Dwi (ASWAJA: Jurnal Pendidikan dan Keislaman, 2023)
The study involves parents from underprivileged families in parenting education, aiming to examine the implementation of the inquiry learning strategy. Participants are recipients of the PKH social assistance. The background of this study stems from their lack of knowledge about effective parenting methods. Utilizing a descriptive qualitative method, this research explores field realities related to social and humanitarian issues. Techniques such as observation, interviews, and document studies were used to gather information. The results show that the planning of the inquiry learning strategy does not always align with the ideal steps. Its implementation often does not fully follow the inquiry steps and requires a special approach for participants from impoverished families. However, this strategy significantly improves participants' understanding of parenting, evident from the positive changes in their parenting methods. This study contributes to the literature on the Family Hope Program, focusing on parenting aspects that have not been extensively researched before. It provides new insights for family empowerment practitioners, highlighting the need for a specialized approach in education for underprivileged families